Anti-rotavirus antibody in cerebrospinal fluid. Issue 3 (March 1987) - Ushijima, H; Araki, K; Abe, T; Shinozaki, T
Abstract : Ten infants with benign convulsions associated with rotavirus gastroenteritis had no specific antibodies in cerebrospinal fluid by enzyme linked immunosorbent assay (ELISA). On the other hand, eight of 173 patients with other neurological diseases had specific IgG, IgA, or IgM antibodies. The reason for positive ELISA results is discussed.